COMPLEX TREATMENT OF COXARTHROSIS IN ADOLESCENTS WITH JUVENILE RHEUMATOID ARTHRITIS - O. A. Malakhov; E. I. Alekseeva; S. J. Morev; O. O. Malakhov; S. I. Valieva; T. M. Bzarova; R. V. Denisova; T. V. Sleptsova; E. V. Mitenko; K. B. Isaeva; L. A. Semenova; E. I. Zelenkovich; et al. (Вопросы современной педиатрии, 2012)
The results of surgical treatment of 34 patients with coxarthrosis due to juvenile rheumatoid arthritis (JRA) are shown in this article. The operations with endoprosthetics methodic were performed in the department of traumatology and orthopaedics of the Scientific Centre of Children Health RAMS since 2008 till 2012. The aim of the study was to evaluate the efficacy of surgical treatment and influence of this procedure on patients life quality. The main presenting complaints were pain and motion limitations in hip joints, differences in extremities length, limping, support disability and lower extremity dysfunction, which makes movement without additional support impossible in 90% of all cases. The indications to the total endoprosthetic hip joint replacement (TEHJR) in adolescents withjuvenile arthritis are represented. The special features of TEHJR in young patients with JRA. The assessment of X-ray pictures during the follow-up examinations showed adequate positioning of endoprosthesis components. One year after the surgical operation the mean level of points according to specialized questionnaire HHS was 88 (87; 89) points (Me [25;75]) (comparing with 55 [51; 58] before the operation, [p < 0,001]), and according to the questionnaire СHAQ — 0,4 (0,3; 0,5) points (comparing with 2,6 [2,3; 2,8] before the operation, [p < 0,001]). This facts confirm the efficacy of the performed treatment and significant improvement in functioning of operated joints and patients life quality. The marked correction of the lower limbs deformations and the normal or near-normal physiological functioning were achieved.